Research through Design as a transformative approach - Vilja Larjosto (Spatial transformation: Processes, strategies, research design, 2022)
New and experimental research methods to understand and co-steer processes of spatial transformation are called for. From the perspective of designing urban landscapes this paper draws a connection between Research through Design and transformative science. (Urban) landscapes constantly undergo (spatial) transformation, and not only have landscape architects always dealt with perpetual change, they increasingly often catalyze it. Designing is an integrative activity and the central means of the discipline to understand issues and draw up possible solutions. Furthermore, design often reaches out to other disciplines, involves multiple participants, and can be paradigm shifting. Research through Design is an increasingly acknowledged approach in landscape architectural research. With regard to the procedures, characteristics and goals of knowledge production, this paper presents commonalities between Research through Design and transformative research, highlighting the integrative and projective nature of designing. In conclusion, I suggest positioning Research through Design among the methods of transformative research.
urn:nbn:de:0156-08911702; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Research through Design; urban landscape; spatial transformation; transformative research; integrative method